Designing an Internet of Things-Based Fire and Gas Leak Detection System - M Adamu Islam Mashuri; Binti Kholifah; Faris Abdi El Hakim (Universitas Negeri Surabaya, 2025)
LPG currently plays a crucial role in daily human activities, both in households and industries. However, gas leaks from LPG cylinders have often led to fire incidents, primarily due to undetected gas emissions. To address this issue, a real-time gas and smoke detection system has been developed using the MQ-2 gas sensor and the ESP32 microcontroller. The system is designed to monitor gas concentration levels and provide early warnings through the Blynk application on smartphones, utilizing the Internet of Things (IoT) concept. The system can detect dangerous gas concentrations above 80 ppm and responds by activating a buzzer and LED indicators. In addition, warning notifications are sent to the user’s smartphone. Test results show the system can accurately detect gas within a 10 cm radius of the sensor, with wireless notification capabilities reaching up to 500 meters. The system proves to be effective in enhancing safety and minimizing fire risks caused by undetected LPG leaks.